2019
DOI: 10.1016/j.rmed.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and immunity in IPF pathogenesis and treatment

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, and ultimately fatal, chronic interstitial lung disease characterized by enhanced extracellular matrix deposition. Repetitive alveolar epithelial injury triggers the early development of fibrosis. These injuries, in combination with dysregulated wound repair and fibroblast dysfunction, lead to ongoing tissue remodelling and fibrosis seen in end-stage pulmonary fibrosis. Although the exact etiology in IPF is unknown and probably diverse, all stages of fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
267
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(281 citation statements)
references
References 213 publications
(269 reference statements)
9
267
1
4
Order By: Relevance
“…We thus suggest that nintedanib has a powerful anti-inflammatory effect on peritoneal fibrosis. These results are consistent with its suppression of inflammation in animal models of IPF and renal fibrosis [9,25]. The protective effect of nintedanib from inflammation may be through its inhibition of multiple RTKs and Src, and subsequently, inactivation of their downstream signaling pathways, such as STAT3 and NF-κB.…”
Section: Discussionsupporting
confidence: 77%
“…We thus suggest that nintedanib has a powerful anti-inflammatory effect on peritoneal fibrosis. These results are consistent with its suppression of inflammation in animal models of IPF and renal fibrosis [9,25]. The protective effect of nintedanib from inflammation may be through its inhibition of multiple RTKs and Src, and subsequently, inactivation of their downstream signaling pathways, such as STAT3 and NF-κB.…”
Section: Discussionsupporting
confidence: 77%
“…7 It remains to be resolved as to what are the key sentinel cells in the lung: Immune and/or stromal, whether fibrosis and inflammation arise in series or in parallel and to what extent they are mutually dependent. [8][9][10] IL11 is a member of the IL6 family of cytokines and secreted by resident fibroblasts in response to profibrotic stimuli. IL11 binds to its specific receptor subunit Interleukin 11 receptor subunit alpha (IL11RA), which is highly expressed on stromal cells (eg, fibroblasts and smooth muscle cells) but not on immune cells, that then signals via the ubiquitously expressed gp130 receptor.…”
Section: Introductionmentioning
confidence: 99%
“…While fibroblasts have been implicated in inflammation-associated pathology of rheumatoid arthritis, colitis and IPF (7,(15)(16)(17)(18), it has not been shown conclusively whether the stroma is a modifier or primary driver of the inflammatory response. In the BLM model of lung fibrosis, we found that the deletion of IL11 signaling in fibroblasts alone is sufficient to protect mice from inflammation in the lung.…”
Section: Combined Results and Discussionmentioning
confidence: 99%
“…In recent years, a primary immune role for Th2 polarized T cells and the Th2 cytokine IL13 gained favor in IPF fibrogenesis but targeting IL13 in clinical trials was ineffective (5). It remains to be resolved as to what are the key sentinel cells in the lung, immune and/or stromal, and how fibrosis and inflammation arise temporally: in series, in parallel or independently (6,7). IL11 is a member of the IL6 family of cytokines that share the use of the GP130 receptor as part of their multimeric receptor-ligand complexes for signal transduction.…”
Section: Introductionmentioning
confidence: 99%